Environmental issues in economic partnership agreements: Implications for developing countries - Beatrice Chaytor (International Centre for Trade and Sustainable Development (ICTSD), 2009)
This issue paper, titled 'Environmental Issues in Economic Partnership Agreements: Implications for Developing Countries', and written by Mrs. Beatrice Dove-Edwin, is a contribution to that process. The paper exhaustively reviews all rules related to trade and environment in several of the already signed EPAs. The aim of the paper is to enable ACP countries to understand how trade policy related to the environment has been introduced in EPAs, and how those policies might impact sustainable development in ACP countries. The paper starts by presenting the current European approach on trade and environment in those agreements. More specifically, it addresses the current state of negotiations, analyses precise proposals made, and explores some of the implications of introducing environmental issues in the EPAs ...
Keywords: 330